منهج القرآن الكريم في التعامل مع المستهزئين - ربوزي, سمير (جامعة الوادي - University of Eloued, 2020)
يعتبر الاستهزاء بالدين وبأهله من أعظم الجنايات التي جاءت الشرائع السماوية بتحريمها، وشهد العلم والواقع على خطورتها وشدة ضررها على الأفراد والمجتمعات؛ ولهذا كثُرت الدراسات حوله هذه الآفة، وتركَّز معظمها حول حكم الاستهزاء بالدين، وأساليبه، وبعض المسائل المتعلقة به الأخرى. ويتناول هذا البحث جانبا هامّا من جوانب هذا الموضوع، يَعتبر الباحث أنه أهم هذه الجوانب، وأشرفها على الإطلاق، ألا وهو منهج القرآن الكريم في التعامل مع المستهزئين. Abstract Mocking religion and religious people is one of the major crimes which the divine religions prohibited. Moreover, knowledge and reality attest to its danger and harm upon individuals and societies. Hence the plethora of studies concerning this flaw. Most of them focused on the ruling regarding mocking religion, its procedures and some other issues related to it. This study deals with an important aspect of this topic, which the researcher considers as the most important and absolutely the most honorable of them; it is the methodology of the Holy Qur’an in dealing with mockers.
مقال في مجلة الشهاب بجامعة الوادي
Keywords: منهج؛ القرآن الكريم؛ التعامل؛ المستهزئين